2002
DOI: 10.1046/j.1440-1789.2002.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological studies of peripheral neuropathy in Churg–Strauss syndrome

Abstract: Clinicopathological studies were performed on the visceral organs and the sural nerve of a male patient with Churg-Strauss syndrome (CSS) in order to understand the mechanisms of peripheral nervous system damage. A 67-year-old man, with a 2-year history of bronchial asthma, developed acutely painful paraplegia and dyspnea. Laboratory data showed a leukocytosis, an elevated serum creatinine kinase (CK) and marked eosionophilia. Autoantibodies including p- and c-ANCA were negative. Electrophysiological studies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Unfortunately, ANCA results were not given, but six cases showed necrotizing vasculitis and 8 cases showed extravascular eosinophilic infiltrates, but only one patient presented an overlap of necrotizing vasculitis and extravascular eosinophilic infiltrates. Nagashima et al [24] reported an ANCA-negative patient with CSS in whom fibrinoid necrosis was shown in a biopsy from intestinal samples, but not in a biopsy from the sural nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, ANCA results were not given, but six cases showed necrotizing vasculitis and 8 cases showed extravascular eosinophilic infiltrates, but only one patient presented an overlap of necrotizing vasculitis and extravascular eosinophilic infiltrates. Nagashima et al [24] reported an ANCA-negative patient with CSS in whom fibrinoid necrosis was shown in a biopsy from intestinal samples, but not in a biopsy from the sural nerve.…”
Section: Discussionmentioning
confidence: 99%
“…In our 3 cases, pathological findings were essential for the diagnosis, and crucial in selecting the proper treatment in the 2 cases primarily expressing AIDP. The pathological findings of the sural nerve biopsies in cases 1 and 5, and muscle biopsy of rectus femoris in case 3, were compatible with eosinophilic necrotizing vasculitis of CSS [1,2,7,9].…”
Section: Discussionmentioning
confidence: 77%
“…There are not many articles describing CSS-associated neuropathy. These reports describe CSS-associated neuropathy in the relation to systemic small-vessel vasculitis, Wegener's granulomatosis and microscopic polyangiitis [4,5], or with central nervous system involvement [6], or present a single case [7,8];…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uma de nossas pacientes apresentou acidente vascular cerebral isquêmico, sem seqüela. Um estudo com 47 pacientes mostrou que 53,2% apresentavam neuropatia sendo 68% mononeuropatia múltipla e 24% polineuropatia distal simétrica (11) . Guillevin, entretanto, não encontrou polineuropatia progressiva bilateral em sua série (9) ; em nossa casuís-tica todos os pacientes apresentaram mononeuropatia múltipla, grave, sendo necessário a introdução de ciclofosfamida em dois casos para controlar os sintomas.…”
Section: Relato De Casounclassified